2023
DOI: 10.1021/acs.jpca.2c08035
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Kinetics on the C7H7 Potential Energy Surface under Combustion Conditions

Abstract: The automated kinetics workflow code, KinBot, was used to explore and characterize the regions of the C 7 H 7 potential energy surface that are relevant to combustion environments and especially soot inception. We first explored the lowest-energy region, which includes the benzyl, fulvenallene + H, and cyclopentadienyl + acetylene entry points. We then expanded the model to include two higher-energy entry points, vinylpropargyl + acetylene and vinylacetylene + propargyl. The automated search was able to uncove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…They suggested a path to formation of vinylcyclopentadienyl via the reaction of cyclopentadienyl with acetylene or vinyl radical. The theoretical results of Marti ́et al 54 and Mao et al 56 indicate that, at temperatures above 1000 K, vinylcyclopentadienyl can be formed from the reaction of cyclopentadienyl with acetylene. At temperatures of 1500 K and above, the main products are fulvenallene + H via vinylcyclopentadienyl as an intermediate.…”
Section: Vinylcyclopentadienylmentioning
confidence: 99%
See 4 more Smart Citations
“…They suggested a path to formation of vinylcyclopentadienyl via the reaction of cyclopentadienyl with acetylene or vinyl radical. The theoretical results of Marti ́et al 54 and Mao et al 56 indicate that, at temperatures above 1000 K, vinylcyclopentadienyl can be formed from the reaction of cyclopentadienyl with acetylene. At temperatures of 1500 K and above, the main products are fulvenallene + H via vinylcyclopentadienyl as an intermediate.…”
Section: Vinylcyclopentadienylmentioning
confidence: 99%
“…Minor channels include vinylacetylene + propargyl, benzyl, tropyl, and 1-or 2-ethynylcyclopentadiene + H. 54,58 All of these channels proceed through vinylcyclopentadienyl, 54,58 but 1-and 2-ethynylcyclopentadiene are only produced through the decomposition of benzyl. 54,74 Vinylcyclopentadienyl is also predicted to be produced from fulvenallene + H at temperatures of 1500 K and lower. 54 Jin et al 55 experimentally demonstrated a route to vinylcyclopentadienyl via the reaction of vinylacetylene with propargyl, which produces benzyl as a minor product.…”
Section: Vinylcyclopentadienylmentioning
confidence: 99%
See 3 more Smart Citations